Behavioral responses and starvation survival of Daphnia magna exposed to fluoxetine and propranolol. (November 2018) - Nielsen, Majken Elley; Roslev, Peter
Abstract: Fluoxetine and propranolol are neuroactive human pharmaceuticals that occur frequently as pollutants in surface waters. The potential effects of these pharmaceuticals on aquatic organisms have raised concern but many adverse effects are not well characterized for a broad range of concentrations and endpoints. In this study, 6 biological parameters in the freshwater Cladoceran Daphnia magna were compared for their responses to fluoxetine or propranolol exposure: mobility (dichotomous response), active swimming time, swimming distance, swimming velocity, swimming acceleration speed, and survival in the absence of food (starvation-survival). Changes in swimming behavior was quantified by video tracking followed by image analyses at six exposure concentrations between 100 ng/L and 10 mg/L. Active swimming time and swimming distance were the most responsive parameters among the behavioral traits. Sublethal exposure concentrations resulted in nonmonotonic responses and behavior profiling suggested that fluoxetine and propranolol stimulated swimming activity at 1–10 μg/L whereas lower (0.1–1 μg/L) and higher exposure concentrations (>100 μg/L) inhibited swimming activity. The ability to survive in the absence of food when exposed to fluoxetine or propranolol resulted in EC50 and EC10 values that were lower than for swimming behavior (EC50 of 0.79–0.99 mg/L; EC10 of 1.4–2.9 μg/L). Starvation-survival appeared to be a potentially simple and sensitive endpoint for adverse effects in D. magna at intermediate exposure concentrations. Nonmonotonic behavioral responses at low exposure concentrations and decreased ability to survive starvation should be considered in assessment of adverse effects of pharmaceuticals to freshwater invertebrates. Graphical abstract: Image 1 Highlights: Fluoxetine and propranolol affected behavior and starvation-survival in D. magna. Swimming activity showed inhibition at exposure concentrations of 0.1–1.0 μg/L. Swimming activity was stimulated at exposure concentrations of 1–10 μg/L. Starvation-survival is a potentially simple and sensitive endpoint in D. magna. Behavioral effects of pharmaceuticals to D. magna are environmentally relevant.